Khilafiyah Dan Perbandingan Mazhab - Sumartini; Dahlan Lama Bawa (Jurnal Pendidikan Agama Islam, 2025)
This study examines the concept of khilafiyah (juristic disagreement) and the comparison of Islamic legal schools (madhhab) as well as their implications for Muslim religious life. Khilafiyah is understood as differences of opinion among mujtahid scholars in determining Islamic legal rulings on issues that lack definitive textual evidence, allowing diverse methodological approaches in ijtihad. This research employs a library research method by analyzing classical and contemporary literature on fiqh and ushul al-fiqh. The findings indicate that khilafiyah has been an integral part of Islamic scholarly tradition since the era of the Prophet’s companions and later developed through various schools of Islamic law. The main principles in addressing khilafiyah include recognizing the relative nature of ijtihad, upholding ethical conduct and tolerance in disagreement, and prioritizing public interest (maslahah). Furthermore, differences among legal schools in matters of worship and social transactions demonstrate the flexibility and dynamism of Islamic law. Therefore, a comprehensive understanding of khilafiyah and madhhab comparison is essential for fostering a moderate, tolerant, and wise religious attitude among Muslims.